Medical alchemy and quintessence in renaissance florence: the Alchemist’s laboratory painting of Johannes Stradanus (1570) - Georgiana D. Hedesan (BJHS Themes)
In 1570, Johannes Stradanus (1523–1605), a Flemish-born artist settled in Florence, produced two paintings meant to adorn the new Studiolo of Prince Francesco I de’ Medici (1541–87). The best-known painting is The Alchemist’s Laboratory, a depiction of the laboratory then existing at the Palazzo Vecchio. The laboratory was set up by Cosimo I (1519–74), the first grand duke of Tuscany. His son Francesco was also enthusiastic about it: Stradanus’s painting portrays the prince working on the premises amongst other artisans. This paper will present the laboratory, instruments and practices by linking them with a specific form of alchemy popular in the period, quintessence alchemy. I will also discuss the extent to which Stradanus’s depiction may be deemed ‘realistic’, relating it to its underlying ideology as well as other contemporary representations.